SEMIOTIKA SIMBOL KOMUNIKASI NON VERBAL JAMAAH AN-NADZIR DALAM MENYEBARLUASKAN IDEOLOGI ISLAM DI KABUPATEN GOWA - Juliadi Juliadi; Hafied Cangara; Tuti Bahfiarti (KAREBA : Jurnal Ilmu Komunikasi, 2018)
ABSTRACTAn-Nadzir congregation is an Islamic community based in Gowa District. An-Nadzir's da'wah method is based on the action of examples and symbols. Their symbols include; Symbols of clothing, symbols of worship movements and symbols of society. This research is intended to know, analyze, and explain the meaning of symbols of An-Nadzir and methods of da'wah An-Nadzir. This research use desciptive qualitative approach. Data collection is done through observation and in-depth interviews with the leadership and members of An-Nadzir. The data were analyzed by using semiotic analysis to study the meaning of An-Nadzir symbols through Roland Barthes meaning analysis model, meaning denotation, connotation, myth and ideology. The results show that the symbols of An-Nadzir contain philosophical, cultural and sociological meaning based on the sunnah of Prophet SAW. An-Nadzir clothing symbols range; cloak, turban, beard and long hair that colored. Symbols of worship movement and symbol of the way of society which is contained in the concept of exemplary action. Hopefully, with this research will be known the form of missionary movement of An-Nadzir through symbols and meanings contained in it. Keywords: semiotics, An-Nadzir symbols, meaning ABSTRAK Jamaah An-Nadzir merupakan komunitas Islam yang bermarkas di Kabupaten Gowa. Metode dakwah An-Nadzir berbasis pada aksi keteladan dan simbol-simbol. Simbol mereka meliputi; simbol pakaian, simbol gerakan ibadah dan simbol cara masyarakat. Penelitian ini bertujuan untuk mengetahui, menganalisis, dan menjelaskan makna simbol-simbol An-Nadzir dan metode dakwah An-Nadzir. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Pengumpulan data dilakukan melalui observasi dan wawancara mendalam dengan pimpinan dan anggota An-Nadzir. Data dianalisis dengan menggunakan analisis semiotika untuk mengkaji makna simbol-simbol An-Nadzir melalui model analisis makna Roland Barthes makna tanda denotasi, konotasi, mitos dan ideologi. Hasil penelitian menunjukkan bahwa simbol-simbol An-Nadzir mengandung makna filosofis, budaya dan sosiologis yang berbasis pada sunnah-sunnah Nabi SAW. Simbol pakaian An-Nadzir meliputi; jubah, surban, janggut dan rambut panjang yang dipirang. Simbol gerakan ibadah dan simbol cara bermasyarakat yang tertuang dalam konsep aksi keteladanan. Diharapkan, dengan penelitian ini akan diketahui bentuk gerakan dakwah An-Nadzir melalui simbol serta makna yang terkandung di dalamnya.